Genetic parameters and gains with the selection of fig tree genotypes - Almeida, Patrícia de [UNESP]; Pavan, Bruno Ettore [UNESP]; Rodrigues, Maria Gabriela Fontanetti [UNESP]; Gaspar, Guilherme de Freitas [UNESP]; Giro, Leonardo de Paula [UNESP]; Silva, Renan Furquim da [UNESP] (Universidade Estadual de Maringa, 2022)
Fig tree (Ficus carica L., Moraceae), which originated in the Mediterranean Basin, is one of the many fruit trees grown in Brazil, with ‘Roxo-de-Valinhos’ being the exclusively used cultivar. In this context, research aimed at the improvement of this species to develop highly resistant and adaptable cultivars is paramount. Thus, the present study aimed to maintain fig accessions in an in vivo active germplasm bank (AGB) at the Faculty of Engineering of Ilha Solteira (FEIS), São Paulo State University (UNESP), as well as to characterize the agronomic traits of these accessions based on quantitative descriptors of genetic parameters and observe gains with the selection of specific genotypes to illustrate the AGB in terms of genetic variability. A total of 36 F. carica genotypes were evaluated in the field at the Teaching, Research and Extension Farm (FEPE) of the FEIS, UNESP. Qualitative traits, fruit parameters (e.g., insertion of the first fruit, fruit stalk length, fruit length, fruit diameter, and average fruit mass), and accumulated plant dry mass were measured. In addition, genetic parameters, variance components, and descriptive statistics, including genetic and environmental variances, heritability and average heritability of clones, coefficients of genotypic and environmental variation and their ratio (CVg%⁄CVe %), general average, and selection gain, were evaluated. The selected fig tree accessions showed genetic variability in the assessed traits, exhibiting good heritability and achieving selection gains. For instance, the first 10 classified clones exhibited a heritability of 80.2% and achieved a selection gain of 98% for accumulated plant dry mass. Therefore, the maintenance of in vivo AGBs allows agronomic studies, offering promising results for continuing the breeding programs and preserving the genetic variability of species.
Keywords: breeding; Ficus carica L; in vivo conservation